Auditory Stimulation Training With Technically Manipulated Musical Material in Preschool Children With Specific Language Impairments: An Explorative Study - Roden, Ingo; Früchtenicht, Kaija; Kreutz, Gunter; Linderkamp, Friedrich; Grube, Dietmar (Frontiers in Psychology, 2019)
Auditory stimulation training (AST) has been proposed as a potential treatment for chil-dren with specific language impairments (SLI). The current study was designed to test this as-sumption by using an AST with technically modulated musical material (ASTM) in a random-ized control group design. A total of 101 preschool children (62 male, 39 females; mean age = 4.52 years, SD = 0.62) with deficits in speech comprehension and poor working memory ca-pacity were randomly allocated into one of two treatment groups or a control group. Children in the ASTM group (n = 40) received three 30-minute sessions per week over 12 weeks, whereas children in the comparison group received pedagogical activities during these intervals (n = 24). Children in the control group (n = 37) received no treatment. Working memory, phoneme dis-crimination and speech perception skills were tested prior to (baseline) and after treatment. Chil-dren in the ASTM group showed significantly greater working memory capacity, speech per-ception, and phoneme discrimination skills after treatment, whereas children in the other groups did not show such improvement. Taken together, these results suggest that ASTM can enhance auditory cognitive performance in children with SLI.